The Paradigm of Pregressivism: Strengthening Education in The Era of Merdeka Belajar - Nuha, Moch. Syihabudin; Gustama, Rosyid Arfan (Sanskara Pendidikan dan Pengajaran, 2024)
Based on Law No. 20 of 2003 concerning the National Education System, it is stated that education is an educational endeavor carried out through improving the learning atmosphere in the classroom and proactive learning that prioritizes self-potential, spiritual, self-control, personality, intelligence, noble character, and skills needed by himself, the surrounding community and the nation and state. Until now, the latest curriculum can only answer this law, namely the Merdeka Belajar curriculum. The Merdeka Belajar curriculum is a curriculum that gives freedom to teachers and schools to develop the potential of students optimally, according to the needs and interests and talents of students, so this is in line with the mandate of the Law. This is also in line with one of the paradigms or philosophies of education, namely the paradigm of progressivism. Progressivism opposes the implementation of traditional education. The progressive school supports the implementation of education that is centered on student participants and develops their various abilities as provisions for facing social life in their environment. This means that progressivism is one of the schools that wants progress, which will bring about a change. Progressivism highly values a person's ability to solve problems through the experiences that everyone has. The research method used in this research is a literature study by collecting sources of journals, books and related articles, then understanding, processing and drawing conclusions. The results of this research show that progressivism has made a major contribution to the world of education in Indonesia. This school has laid the foundations of independence and freedom to students. Students are given freedom, both in theory and practice, to develop talents and skills latent in themselves without being hampered by obstacles made by others.